Arahan Pengembangan Sentra Industri Garam di Kecamatan Arungkeke, Kabupaten Jeneponto - Muhammad Albab Gunawan; Ihsan Ihsan; Abdul Rachman Rasyid (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Arungkeke subdistrict is one of the main producers of national salt production in fulfilling national salt needs, especially in South Sulawesi. To fullfill industrial and consumption needs efforts are needed to maximize the potential in salt-producing centers. The aim of this study is to determine the extent of the potential for extensification of salt fields, the potential for the formation of salt industrial clusters and the direction for the development of salt pond centers. This research was conducted in Arungkeke District, Jeneponto Regency from June 2019 until February 2020 (9 months). This study uses a literature approach and field research. The analytical method used is descriptive quantitative and qualitative analysis, as well as spatial analysis. The results of the analysis showed that the area of the potential for extensification of the salt ponds reaches 19.55 km2. The average distance between a point (industry) and its closest point is 0.036 km. As many as 77.77% or 224 points (industry) have a distance from the closest industry that is less than this average distance. This condition is in accordance with the theory of the cluster life cycle according to Menzel and Fornahl, which has the potential to become an industrial cluster. The directions for the development of salt industrial centers in the future are: 1) the need for extensification of salt ponds on suitable land; 2) providing distributors of production equipment; and 3) cooperating with universities or the private sector, either in the form of technical assistance for production or product innovation, business management and marketing.